Incidence and risk factors of early thromboembolic events after mechanical heart valve replacement in patients treated with intravenous unfractionated heparin. Issue 20 (28th May 2009) - Allou, N; Piednoir, P; Berroëta, C; Provenchère, S; Ibrahim, H; Baron, G; Montravers, P; Iung, B; Philip, I; Ajzenberg, N
Abstract : Objective: To evaluate the incidence and risk factors, including timing and intensity of anticoagulation, of early thromboembolic events (TE) after mechanical heart valve replacement (MHVR) in patients treated by intravenous unfractionated heparin (IVUH). Design: Prospective observational study, conducted between December 2005 and May 2007. Setting: Haemostasis laboratory, surgical intensive care unit and ward in a university hospital. Patients: Three hundred consecutive patients undergoing MHVR. Mitral or double MHVR was performed in 149 patients, and aortic MHVR in 151 patients. Postoperative anticoagulation was achieved with continuous IVUH according to a standardised protocol. The timing of efficient anticoagulation was recorded for each patient. Main outcome measures: The end point was the occurrence of any arterial TE from day 1 to day 30. Transoesophageal echocardiography was systematically performed after mitral MHVR. Results: Early TE occurred in 22 patients (14.8%; 95% CI 9% to 20%) after a mitral or double MHVR and in two patients (1.3%; 95% CI 0% to 3%) after an aortic MHVR (p = 0.005). After adjustment for diabetes mellitus (adjusted OR (aOR) = 3.3; 95% CI 1.0 to 10.9, p = 0.049), and for the presence of predisposing factors (heparin-induced thrombocytopenia or bradycardia requiring definitive pacemaker implantation) (aOR = 12.8; 95% CI 3.1 to 53.3, p<0.001), effective anticoagulation on day 3 was a protective factor (aOR = 0.28; 95% CI 0.1 to 0.8, p = 0.018) for early TE after mitral MHVR. Conclusions: Despite the use of IVUH, the rate of early TE after mitral MHVR remained elevated. These results suggest that early effective anticoagulation is required after mitral MHVR, since inappropriate anticoagulation on day 3 was significantly associated with early TE.